2021
DOI: 10.1097/cad.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing calcium channel blockers: may be sensible combination with erlotinib for non-small cell lung cancer

Abstract: The Journal is a member of the Committee on Publication Ethics (COPE) which aims to define best practice in the ethics of scientific publishing (www.publicationethics.org).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The 1-year OS rate for CCB users and nonusers was 78.3% and 39.7%, respectively, whereas the 2-year PFS rate was 44.4% and 8.3%, respectively. 19 Our study showed similar results, with the estimated median PFS and OS for the CCBs-/EGFR-TKIs + group being 7.70 and 12.17 months, respectively; the results were significantly different from those of the CCBs + /EGFR-TKIs + group (10.43 and 18.07 months, respectively). Therefore, concomitant use of CCBs and EGFR-TKIs can improve PFS and OS.…”
Section: Discussionsupporting
confidence: 80%
“…The 1-year OS rate for CCB users and nonusers was 78.3% and 39.7%, respectively, whereas the 2-year PFS rate was 44.4% and 8.3%, respectively. 19 Our study showed similar results, with the estimated median PFS and OS for the CCBs-/EGFR-TKIs + group being 7.70 and 12.17 months, respectively; the results were significantly different from those of the CCBs + /EGFR-TKIs + group (10.43 and 18.07 months, respectively). Therefore, concomitant use of CCBs and EGFR-TKIs can improve PFS and OS.…”
Section: Discussionsupporting
confidence: 80%
“…They showed that amlodipine decreases PD-L1 expression posttranslationally by blocking intracellular calcium flux, and it also facilitates the autophagic degradation of PDL-1. In our previous study, we showed that amlodipine and erlotinib have additive effects in metastatic nonsmall cell lung cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous retrospective studies, we have shown that especially regorafenib and amlodipine combination increases the effectiveness at colorectal cancer [2]. In out another study, we showed that amlodipine inproves outcomes of erlotinib in non-small cell lung cancer [3]. In preclinical studies, amlodipine has been shown to inhibit the growth of gastric cancer cell lines.…”
Section: Introductionmentioning
confidence: 88%